(untitled) - Khan, Hena; Jaleel, Aaliya (New York, 2019)
As a young girl observes that each of six women in her life wears her hijab and hair in a different way, she considers how to express her own style one day.
Keywords: Fiction; Muslims; Fiction; Individuality; Fiction; Clothing and dress; Fiction; Hijab (Islamic clothing); Stories in rhyme; Individuality; Muslims; Juvenile fiction; Juvenile fiction; Clothing and dress; Juvenile fiction; Hijab (Islamic clothing; Stories in rhyme; Fiction